2022
DOI: 10.3389/fcvm.2022.971848
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial appendage flow velocity predicts recurrence of atrial fibrillation after catheter ablation: A systematic review and meta-analysis

Abstract: PurposeThere is increasing evidence that left atrial appendage flow velocity (LAAFV) is linked to the recurrence of atrial fibrillation (AF) after catheter ablation (CA), suggesting the potential predictable significance of LAAFV in this setting. We performed a systematic review and meta-analysis to assess whether LAAFV is association with AF recurrence after CA.MethodsUp to May 1, 2022, six databases (PubMed, EMBASE, Web of Science, Cochrane Library, Scopus, and CINAHL) were searched for literature reporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“… [13] As impaired LA function can precede LA expansion, particularly in patients with paroxysmal AF, LAAV is a more sensitive predictor for sinus rhythm maintenance and AF recurrence than LA size. [8] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… [13] As impaired LA function can precede LA expansion, particularly in patients with paroxysmal AF, LAAV is a more sensitive predictor for sinus rhythm maintenance and AF recurrence than LA size. [8] .…”
Section: Discussionmentioning
confidence: 99%
“… [6] , [7] The average left atrial appendage emptying velocity (LAAV) is a recognized marker of LAA function considering contractility, stunning, and fibrosis. [8] Despite LAAV serving as a marker of LAA function and being able to be easily calculated by Doppler during pre-ECV transesophageal echocardiogram (TEE), there is a paucity of data on the role of LAAV in predicting the risk of AF recurrence after ECV. Thus, we performed this study to evaluate whether LAAV is associated with an increased risk of AF recurrence after ECV.…”
Section: Introductionmentioning
confidence: 99%
“…Ueno et al 7 revealed that LAAV < 37.5 cm/s could predict AF detected with an insertable cardiac monitor in patients with cryptogenic stroke. Two large meta-analyses have also shown that LAAV is one of the factors that increases the likelihood of AF recurrence after catheter ablation 8 , 9 . Raval et al 10 reported that LAAV ≤ 30 cm/s was independently associated with an increased risk of AF recurrence after TEE-guided electrical cardioversion.…”
Section: Introductionmentioning
confidence: 99%
“…So far, only a few studies have mentioned the relationship between left atrial appendage peak flow velocity (LAA-PEV) and persistent AF recurrence (8). However, these studies focused on the link between LAA-PEV and persistent AF recurrence after initial radiofrequency ablation (9), otherwise the correlation between LAA-PEV and paroxysmal AF recurrence after cryoballoon ablation is not established. The STOP Persistent AF Trial demonstrated cryoballoon ablation is safe and effective in treating patients with persistent AF.…”
Section: Introductionmentioning
confidence: 99%